1996
DOI: 10.1021/ma9509927
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Processes in Nonlinear Optical Polyimide Side-Chain Polymers

Abstract: Relaxation processes in nonlinear optical modified polyimide polymers with side-chain azo chromophores having glass transition temperatures in the range of 140 < T g < 170 °C have been studied. The relaxational mechanisms of the side-chain chromophores in these polymers have been investigated above and below the glass transition by second-harmonic decay, dielectric relaxation, and differential scanning calorimetry measurements. The nonexponential relaxation in both the time and frequency domains was modeled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…The DR1-MMA result agrees with the recent work of Kaatz et. al., 12 where they observed that, deep in the glass, chromophore reorientation is more coupled to ␣-type relaxation processes in side-chain NLO polymers than in guest-host systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DR1-MMA result agrees with the recent work of Kaatz et. al., 12 where they observed that, deep in the glass, chromophore reorientation is more coupled to ␣-type relaxation processes in side-chain NLO polymers than in guest-host systems.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have performed relaxation studies [3][4][5][6][7][8][9][10][11][12] at temperatures near and above the glass transition temperature (T g ) that show a direct connection between chromophore reorientation and the long-range ␣-type motion of the polymer backbone. However, other experiments performed at temperatures below the T g show that chromophore reorientation appears to couple to secondary relaxations in guest-host systems.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,17 Here, we utilize an expansion good for higher frequencies, which goes in inverse powers of z:…”
Section: B Leading-term Approximationmentioning
confidence: 99%
“…Heldmann et al 14,15) and Firestone et al 16) studied relaxation of poled order in rigid-like polymers with chromophores rigidly attached to the main-chain. Kaatz et al 17) , Winkelhahn et al 18) and Burland et al 10) have correlated orientational behavior above and below T g quantitatively using established theories for relaxation in glass forming materials. Other groups have thoroughly investigated the typical non-exponential relaxation processes in NLO-polymers below T g 10,19) .…”
Section: General Backgroundmentioning
confidence: 99%